HAK NEGARA DAN MASYARAKAT HUKUM ADAT ATAS HUTAN ADAT - Nadira Apricia (PENERBIT LAFADZ JAYA, 2022)
Indonesia is known to be a country that has a large forest. However, over time, forests in Indonesia have been damaged, reducing the area of forest owned by Indonesia. Many things are the cause of forest destruction in Indonesia, one of which is due to the lack of involvement of local Indigenous Peoples to participate in managing forests. As a society whose life is closest to nature including forests, indigenous peoples should be the most suitable people and have the right to manage and utilize forests. The Government of Indonesia recognizes and respects customary law so that in its development, the Government guarantees the rights and obligations of Indigenous Peoples by issuing regulations and laws on Indigenous Peoples of Law and Customary rights. However, in the regulations and laws that have been established there are thoughts that assume the Government only recognizes Indigenous Peoples and does not recognize the rights of Indigenous Peoples. To ensure the recognition of the rights of Indigenous Peoples of Law, the Government must provide clear legal certainty regarding the right of ulayat to customary forests.